Challenges of integration of Traditional Health Services in Primary Health Care in North Minahasa Regency - Asep Rahman; Hilman Adam; Irny E. Maino (PT. Anagata Sembagi Education, 2025)
Traditional health services are an integral part of the healthcare system, but they have not developed as significantly as other healthcare services. This research aims to investigate the challenges faced in integrating traditional health services into primary healthcare in North Minahasa Regency. The research method used is a case study, employing in-depth interviews with relevant stakeholders involved in traditional health policy and practices. The study seeks to identify potential strategies to address these challenges, including enhancing dialogue and collaboration between both health systems and developing clearer and more inclusive regulations. Based on the interview findings, traditional health services in North Minahasa Regency face significant challenges in terms of legal recognition, a lack of trained personnel, and limited budgetary and regulatory support. Nonetheless, there are substantial opportunities for development, particularly in utilizing medicinal plants and providing skills training, such as acupressure, for the community. Further government support in terms of regulation and funding is necessary to overcome these challenges and promote the broader development of traditional health services.